A successful case of deceased donor liver transplantation for a patient with intrahepatic arterioportal fistula. Issue 13 (31st May 2016) - Takagi, Kosei; Yagi, Takahito; Yoshida, Ryuichi; Shinoura, Susumu; Umeda, Yuzo; Nobuoka, Daisuke; Watanabe, Nobuyuki; Kuise, Takashi; Sui, Kenta; Hirose, Akira; Tsuboi, Makiko; Ogasawara, Mitsunari; et al.
Abstract : Intrahepatic arterioportal fistula (IAPF) is a rare cause of portal hypertension that is often difficult to treat with interventional radiology or surgery. Liver transplantation for IAPF is extremely rare. We report a case of bilateral diffuse IAPF with severe portal hypertension requiring deceased donor liver transplantation (DDLT). A 51‐year‐old woman with no past medical history was admitted to another hospital complaining of abdominal distension and marasmus. A computed tomography scan and digital subtraction angiography indicated a massive pleural effusion, ascites, and a very large IAPF. Several attempts of interventional embolization of the feeding artery failed to ameliorate arterioportal shunt flow. As ruptures of the esophageal varices became more frequent, hepatic encephalopathy worsened. After repeated, uncontrollable attacks of hepatic coma, the patient was referred to our facility for further treatment. Surgical approaches to IAPF other than liver transplantation were challenging because of diffuse collateralization; therefore, we placed the patient on the national waiting list for DDLT. Although her Model for End‐Stage Liver Disease score was relatively low, she received a DDLT 2 months after the waiting period. The postoperative course was uneventful, and the patient was discharged 44 days after her transplant. Liver transplantation may be a valid treatment option for uncontrollable IAPF with severe portal hypertension.